Case report: Personalized adapted motor activity in a COVID-19 patient complicated by critical illness polyneuropathy and myopathy - Crisafulli, Oscar; Baroscelli, Marta; Grattarola, Luca; Tansini, Giuseppe; Zampella, Cristian; D’Antona, Giuseppe (Frontiers in Physiology, 2022)
Background: COVID-19 may require hospitalization in an intensive care unit (ICU) and is often associated with the onset of critical illness polyneuropathy (CIP) and myopathy (CIM). Due to the spread of the disease around the world, the identification of new rehabilitation strategies for patients facing this sequence of events is of increasing importance. Case presentation: We report the clinical presentation and the beneficial effects of a prolonged, supervised adapted motor activity (AMA) program in a highly deconditioned 61-year-old male COVID-19 patient discharged from ICU and complicated by residual CIP and CIM. The program included aerobic, strength, gait, and balance training (1 hour, 2 sessions per week). Measures: Pulmonary (spirometry), metabolic (indirect calorimetry and bioimpedance), and neuromuscular function (electromyography) were evaluated at baseline and after 1 year of training. Results: Relative to baseline, an amelioration of several spirometric parameters such as vital capacity (VC, +40%), total lung capacity (TLC, +25%), and forced expiratory volume in 1 second (FEV1, +28%) was appreciable. Metabolic parameters returned to the physiological range, for instance: body water (60% to 46%), phase angle (3.6° to 5.9°), and respiratory quotient (0.92 to 0.8). Electromyographic parameters were substantially unchanged. The overall amelioration in clinical parameters resulted in a significant improvement of patient autonomy and quality of life. Conclusion: Our results highlight the importance of AMA to counteract respiratory, metabolic, and functional impairments in COVID-19 patients with residual CIM and CIP.